(untitled) (The Pakistan Development Review, 2025)
Khokha (Kiosk) is a major part of informal markets and is widely observed across the globe and in Pakistan. Khokhas are one of the major sources of market-based poverty alleviation and absorb a significant number of labour force. However, on average Khokhas in Pakistan are in shabby states, which arise a question about its regulatory framework. Whether any regulatory framework of Khokhas prevails in Pakistan and to what extent it facilitates or hinders entry. To find an answer to these questions, we collect data from secondary and primary sources and find that, there exists no legal framework to obtain a license for establishing Khokhas in Pakistan. People set up a Khokha with a constant fear of demolishment, fines, confiscation, and arrest. We also find that the harassment of current vendors from public authorities is a major behavioural barrier for prospective entrants. Based on the other countries’ best practices, we propose a detailed set of policies for creating a formal legal framework for khokhas across Pakistan.